IN MEMORY OF ACADEMICIAN OF THE NAS OF UKRAINE VADYM IVANOVYCH LYALKO - Попов, М.О.; Седлерова, О.В.; Хижняк, А.В. (Institute of Geological Sciences, NAS of Ukraine, 2022)
The article highlights the life and scientific legacy of Academician of the National Academy of Sciences of Ukraine Vadim Ivanovich Lyalko, the contribution and significance of his works to the development of the scientific direction of remote sensing of the Earth in solving the tasks of aerospace monitoring of the environment, the nature of resource tasks, and observing global changes in the geosphere.